PERBEDAAN TUMBUH KEMBANG BALITA YANG DI ASUH OLEH ORANG TUA DI RW 02 PONDOK PUCUNG DENGAN BALITA YANG DI TITIPKAN DITEMPAT PENITIPAN ANAK BIG DAY CARE BINTARO TANGERANG SELATAN - Oryza Intan Suri; Antonius Yokobus (Jurnal Kesehatan STIKes IMC Bintaro, 2019)
Delay in growth and development is a serious problem for developed countries and developing countries in the world. The incidence of growth disturbances in children continues to increase seen from the 2010 Population Census Projected Results, in 2014 it is estimated to reach 252.2 million people, and around 82.85 million people (32.9 percent) among them (Indonesian Child Profile, 2015 ) Objective: To find out the differences in toddler growth in foster care by parents in RW 02 Pondok Pucung with toddlers who were entrusted to the day care center of BIG Day Care Bintaro Tangerang, 2018. This study used a quantitative comparative method with cross sectional design. Data collection uses purposive sampling with a sample of 70 samples. The instrument used is DDST. The analysis technique uses the Fisher test. Research Results: Shows there are differences in child development in the category of Social Adaptation Living with parents as many as 16 people (38.1%) and in place for child care 26 people (61.9%). From the results of statistical test data using Chi Square test, the probability value is 0.028 (p value <0.05) which means at α 5%, which means there is a significant relationship. Suggestion: So that mothers and caregivers can provide the right stimulus so that children's growth and development becomes more optimal.